Lesions of either anterior orbitofrontal cortex or ventrolateral prefrontal cortex in marmoset monkeys heighten innate fear and attenuate active coping behaviors to predator threat - Shiba, Yoshiro; Kim, Charissa; Santangelo, Andrea M.; Roberts, Angela C. (Frontiers in Systems Neuroscience, 2015)
The ventral prefrontal cortex is an integral part of the neural circuitry that is dysregulated in mood and anxiety disorders. However, the contribution of its distinct sub-regions to the regulation of negative emotion are poorly understood. Recently we implicated both the ventrolateral PFC (vlPFC) and anterior orbitofrontal cortex (antOFC) in the regulation of conditioned fear and anxiety responses to a social stimulus, i.e. human intruder, in the marmoset monkey. In the present study we extend our investigations to determine the role of these two regions in regulating innate responses and coping strategies to a predator stimulus, i.e. a model snake. Both the vlPFC and antOFC lesioned groups exhibited enhanced anxiety-related responses to the snake in comparison to controls. Both groups also showed a reduction in active coping behavior. These results indicate that the vlPFC and antOFC contribute independently to the regulation of both innate fear and, as previously reported, conditioned fear, and highlight the importance of these regions in producing stimulus-appropriate coping responses. The finding that dysregulation in two distinct prefrontal regions produces the apparently similar behavioral phenotype of heightened negative emotion provides insight into the varied aetiology that may underlie this symptom across a wide variety of neuropsychiatric conditions with implications for personalized treatment strategies.